2013
DOI: 10.19026/rjaset.5.4830
|View full text |Cite
|
Sign up to set email alerts
|

Blind Image Restoration Based on Signal-to-Noise Ratio and Gaussian Point Spread Function Estimation

Abstract: In order to improve the quality of restored image, a blind image restoration algorithm is proposed, in which both the Signal-to-Noise Ratio (SNR) and the Gaussian Point Spread Function (PSF) of the degraded image are estimated. Firstly, the SNR of the degraded image is estimated through local deviation method. Secondly, the PSF of the degraded image is estimated through error-parameter method. Thirdly, Utilizing the estimated SNR and PSF, high resolution image is restored through Wiener filtering restoration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Unfortunately, blind SNR estimation is an open issue in image processing theory. The ratio between maximum and minimum local variances as described in [17] can be used as a rough SNR estimate and it is defined as SNR=10log10(max(δI2)min(δI2))where δI2 is the local variance of image I at position ( i , j ) defined as δI2(i,j)=1(2p+1)(2q+1)k=-ppl=-qq[I(i+k,j+l)-normalμI(i,j)]2where p and q are the sizes of the local area, I is an image formed by the spatiotemporal distribution of the considered shape parameter and μ I the local mean value which is defined as μI=1(2p+1)(2q+1)k=-ppl=-qqI(i+k,j+l)in this study the local area size was defined as p = 2 and q = 2, as suggested in [17]. …”
Section: Foundation Of the Velocity Spectrum Techniquementioning
confidence: 99%
“…Unfortunately, blind SNR estimation is an open issue in image processing theory. The ratio between maximum and minimum local variances as described in [17] can be used as a rough SNR estimate and it is defined as SNR=10log10(max(δI2)min(δI2))where δI2 is the local variance of image I at position ( i , j ) defined as δI2(i,j)=1(2p+1)(2q+1)k=-ppl=-qq[I(i+k,j+l)-normalμI(i,j)]2where p and q are the sizes of the local area, I is an image formed by the spatiotemporal distribution of the considered shape parameter and μ I the local mean value which is defined as μI=1(2p+1)(2q+1)k=-ppl=-qqI(i+k,j+l)in this study the local area size was defined as p = 2 and q = 2, as suggested in [17]. …”
Section: Foundation Of the Velocity Spectrum Techniquementioning
confidence: 99%